PENGARUH KEBIJAKAN DANA DESA TERHADAP JUMLAH PENDUDUK MISKIS PEDESAAN DI INDNESIA - Nisa Erma Fitriana; Riatu Mariatul Qibthiyyah (Jurnal Ekonomi dan Kebijakan Publik Indonesia, 2021)
AbstractIn 2014, the Indonesian government issued Law No. 6 of 2014 concerning Villages, a form of state recognition of villages, specifically in clarifying village authority and functions and strengthening the position of towns and village communities as development targets. One of the objectives of this Village Fund policy is to reduce the rural poverty level in Indonesia. This policy first appeared in the Jokowi-JK era as the central government’s effort in poverty alleviation programs and reducing inequality between rural and urban poverty. In the last nine years, rural poverty has always been higher than urban poverty. This study uses panel data from 514 districts/cities in Indonesia from 2010 to 2018. The results show that in 2015-2018, the Village Fund Policy impacted rural poverty levels using the fixed-effect estimation method. In terms of magnitude, it may signal the inefficiency of the policy. On the other hand, in contrast to Village Fund (DD – Dana Desa), another source of village revenues such as Financial Assistance (BK – Bantuan Keuangan), the transfer fund from district/city governments and provincial government, have a more significant effect on rural poverty.